Professional Efficiency Requirements for Auditors in Accordance with the Eighth International Accounting Education Standard “A field Study at Auditing Companies in Iraq” - Al-Naeemi, Basimah F. (Humanities Journal of University of Zakho, 2018)
The subject of audit quality has been taking inconsideration from many organizations and professional accounting associations, along with seeking research and writing efforts by researchers. The subject of quality of external auditor while has not received such interest. However, the International Federation of Accountants representing by the International Standards Board for Accounting Education activates a special and pioneer role when they issued the eighth international standard for accounting education "Professional Competence for Engagement Partners Responsible for Audits of Financial Statements" that was implemented starting from the second half of 2016. This study dealt with the subject of accounting education in terms of its importance, the most prominent international accounting organizations concerned with accounting education and the International Accounting Standards for Accounting Education along with an emphasis on the eighth international standard of accounting education in terms of its origins, development, its components, and the scope of its application as well as the concept of professional efficiency, its requirements, the way to evaluate, and finally explore the possibility of applying this standard to the auditors who work as partners in the accounting firms (Limited Liability Partnership) in Iraq by testing the hypothesis of this study through a field study.